Ordem e desordens socioambientais na bacia inferior do rio Piauí, em Sergipe - Lima, Elder dos Santos (2012)
This dissertation addresses the universe ofwatersheds as the basic unit of environmental studies and has the catchment area of the resorttowns, and Santa Luzia Indiaroba Itanhy, members of the lower basin of the river Piauí, serving the southern coastal state of Sergipe. The overall objective was to analyze the process and forms of use and occupation of land in pursuit ofsocio reveal order and disorder. The theoretical and methodological was delimited from the Geossistêmico Bertrand model that allowed an analysis articulated between the naturaland anthropogenic lead. Therefore, the integration of the geo-environmental conditions was constituted in analysis of spatial order, while the disorders have been targeted by demographics,the field of livestock, conflicts of shrimp farming, industry and trade, highlighting the environmental impacts of socio-economic activities asresponsible for the process dynamics environment. As a conclusion, the hydrodynamics pretérita was the decisive factor in shaping the coastal plain and the behavioral pattern of rainfall shows good surpluswater in late autumn and winter and moderatesummer disabilities. The parameters, indicators of pollution by organic origin, were found at levels impacting water supplyfor the population. In the evolution of urban and rural population, we found an increase of 0.9% compared to 10:52% of rural population growth. Shrimp farming is an expanding activity in the three counties and has reduced the quality of our riversand lakes by input of organic matter released, causing the eutrophication of waters. In the context of the basin's preeminent urban resort, based on land use, the high concentration and for being a city of the industrial economy, with strongdemand for coastal tourism.